Regulatory Challenges in International Aviation: Indonesia and Russia Compared - Gevan Naufal Wala; Lazarev Viktor Antonovich (Pattimura Legal Journal)
Introduction: The global aviation industry operates within a complex web of international regulatory frameworks that vary significantly from one country to another. This study focuses on the interplay between these frameworks, particularly examining the legal perspectives of Indonesia and the operational experiences of Russian pilots. Understanding these dynamics is crucial for identifying regulatory challenges that affect cross-border aviation operations.